The level of consumers awareness on internet banking / Mastura Muhamat - Muhamat, Mastura (Faculty of Business and Management, 2011)
The purpose of this research is to examine the level of consumer awareness on internet banking and the most factors influencing consumer awareness toward internet banking. It is conducted to determine if there is any relationship between consumer awareness on internet banking and advertisements, publicity and social influences. The researcher chooses to use descriptive research design as a research method and the researcher also use survey in order to collect the data. Data used in this research are primary data and so on secondary data such as journals and articles. The researcher also use structured questionnaire design to obtain the data in order to convenience the respondent to give feedback since most of them bust with their daily life. From the result, researcher found that the most influencing factors contribute to the level consumer awareness on internet banking is social influences, followed by advertisements and publicity. For the last chapter in this research which is include the conclusion and recommendation of the research, the conclusion is to summarize of finding, which will answer to the research questions and research objectives. The recommendations show the way how to increase the level of consumer awareness on internet banking.